No olho do furacão: a circulação das fake news do governo Jair Bolsonaro nas plataformas durante a pandemia da covid-19 - Oliveira, Antonio Peixoto (2021)
The dissertation proposes to analyze the spread of disinformation by the Jair Bolsonaro government about the Covid-19 pandemic in Brazil. O recorte analisa o discurso político de postagens difundidas pelo presidente da república, integrantes e aliados do governo, durante o início da pandemia, de janeiro a março de 2020, até o acontecimento #bolsonaroday, no Twitter, no primeiro de abril – dia da mentira. While the World Health Organization recommended social isolation and prevention measures, the Jair Bolsonaro government tried to minimize the importance of the pandemic and the risks of the disease with misinformation, a characteristic of post- truth, as pointed out by Wicholwski (2017). The circulation of these contents took place in the context of the eye of a hurricane called “infodemia”, characterized by the uncontrolled spread and large proportions of uninformative contents associated with the pandemic and its consequences. This strategy adds to a history of aggressive, polarized and fake news propagator discourse adopted by the political figure of Jair Bolsonaro, who served as federal deputy for nearly three decades before becoming head of state. This climate of polarization and clashes is reaffirmed during the presidential election campaign and the government itself, characterized by the constant practice of polemical statements, dissemination of lies and controversial actions that mobilize sociopolitical crises. The research cutout involves the selection of posts made on social networks and traditional media by the political actors involved, characterized as uninformative content based on fact-checking mechanisms from the agencies Comprova, Fato or Fake and Lupa, as well as fact- checking own. We selected among the contents checked, those that are directly related to the Covid-19 context and organized them in a timeline. Next, we analyzed the typology of fake news based on the categories of Wardle (2017) where we found the presence of misleading, false and out-of-context content, among other types. We elaborated a categorization of the themes present in the content, according to Bardin (1977) and we also verified the recurrence of misinformation with an emphasis on a tone modulation between denial and the normalization of the crisis throughout the period. Through the analysis, it is also observed that the Bolsonaro government adopts the clash through misinformation as a discursive strategy characterized by the polarization of “opponents” in line with recommendations from health agencies and discrediting the press.